Contemporary issues in luxury brand management - Studente, Sylvie; Cattaneo, Eleonora (Abingdon, Oxon ; New York, NY : Routledge, 2023)
This book provides a comprehensive overview of the key themes surrounding luxury brand management and the core issues faced by luxury firms today. The luxury industry has undergone a series of dynamic changes in the past twenty years. Economic trends, digital transformation, and changing consumer habits are creating a new competitive landscape where traditional strategies will not necessarily provide continued growth and profitability. Approaching luxury from a realistic brand management perspective, this book works step-by-step through a typical luxury course structure, covering sustainability, heritage, emerging brands, digital marketing and analytics, curation, intellectual property, and start-ups. Each chapter is illustrated by a relevant international case study and further examples, as well as reflective questions to help gain insight from contemporary practice. With additional PowerPoint slides and a test bank of questions available online, this comprehensive textbook should be core reading for postgraduate students studying luxury brand management or luxury strategy.
Keywords: Luxury goods industry -- Management; Brand name products; BUSINESS & ECONOMICS / Marketing / General; BUSINESS & ECONOMICS / Advertising & Promotion; BUSINESS & ECONOMICS / Marketing / Research